Effect of Ascorbic Acid on Pathogenic Staphylococcus aureus Growth singly and in Combination with Some Antibiotics - Yossef, H. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
One hundred and fifteen isolates of Staphylococcus aureus were isolated from human infected wound and burn. The resistance of this organism for eight commonly used antibiotics was determined by disc diffusion methods.          The minimum inhibitory concentration MIC was determined for each drug by tube dilution method. Results showed significant variations in the MIC values. It was found that two isolates had high resistance for the eight antibiotics used. Effect of ascorbic acid on bacterial growth was studied singly and in combination with antibiotics. Reductions in MIC value were reported for different antibiotics when tested by growth curve method too.